Ard Burdjan or Ard Dobrudjan? [In Bulgarian] - J. Tabov (Venec, 2014)
The famous old map of al-Idrisi in the territory of today Dobrogea has a name which would be written with the Cyrillic alphabet in the form ard Burdzhan. Here is presented the hypothesis that ard brudzhan is obtained by rewriting, as a result of a misreading, of ar Dobrudzha and ard Dobrudzha, and means, respectively, Dobrich and/or Dobrogea.